Adaptation to host-specific bacterial pathogens drive rapid evolution of novel PhoP/PhoQ regulation pathway modulating the virulence. (April 2020) - Raheem, Muhammad Akmal; Xue, Mei; Ahmad, Hafiz Ishfaq; Ahmad, Muhammad Zulfiqar; Tipu, M.Y.; Afzal, Gulnaz; Song, Xiangjun; Rahim, Muhammad Ajwad; Qi, Kezong
Abstract: The presence of the PhoP-PhoQ system is usually different in various bacterial groups, suggesting that PhoP can control the expression of different genes in species. However, little is known about the evolution of the PhoP-PhoQ system among bacterial pathogens. Here, we study the evolution of PhoP and PhoQ regulation in 15 species of Enterobacteriaceae family. We have determined that the regulatory objectives adopted by PhoP and PhoQ are mainly different, due to the result of horizontal gene transfer events and even the change in the genetic content between closely related species. We have compared many possibilities tests (M1 vs. M2 and M7 with M8) to determine the positive selection. Estimating parameters at M1 and M2, with positive selection in M2 of the two proteins. The proportions of positive selection sites significant with ω = 4.53076 for PhoP and ω = 4.21041 PhQ. M8 was significant for PhoP and PhQ proteins. To further confirm the positive selection results, we used the Selecton server to confer positive selection on individual sites using the Mechanistic-Empirical Combination model, and we noticed that several sites had been identified under selection pressure during the evolution. There was a strong indication for the positive selection in bacterial genes of PhoP and PhoQ showed the results. By the use of REL and IFEL, the positive selection for PhoP was detected 14 and 11 sites respectively at different codon positions. The positively selected sites of amino acids such as Arginine, Alanine, Lysine, and Leucine are more important for the production of signals. Our results suggest that the positive selection of PhoP-PhoQ genes in host adaptation during evolution raises an intriguing possibility causes subtle variations in actions of PhoP-PhoQ and also increases the opportunities that cause modification in protein structure for the evolution of increasing pathogenicity in bacterial pathogens. Highlights: The positive selection of PhoP-PhoQ genes in host adaptation caused the subtle variations in actions of PhoP-PhoQ system. The selection pressure on PhoP-PhoQ genes during evolution increased the pathogenicity in bacterial pathogens. The variation or stability in the function of a gene might be due to positive selection. This study facilitates the distinctive approaches for the identification of virulence proteins in bacterial pathogens.